Avaliação do efeito radioprotetor da lidocaína e da histamina em glândulas parótidas de ratos submetidos à radioterapia - Medella Junior, Francisco de Assis Carvalho (2017)
Head and neck radiotherapy often involves major salivary glands, which may result in hyposalivation and xerostomia. Qualitative and quantitative salivary dysfunctions predispose the individual to changes in the oral mucosa and teeth, cause impairment to oral functions and negative impact on quality of life. In the first article of this study we carried out a literature review addressing the therapeutic management of salivary dysfunction. Established in the literature treatment modalities were reviewed, as well as new options still under investigation. The second paper describes an experimental study, which aimed to evaluate the radioprotective effect of histamine and lidocaine on morphological changes induced by radiation in parotid glands of rats. Fifty-six Wistar rats were divided into four groups: Control, Irradiated, Lidocaine and Histamine. The experimental groups were submitted to ionizing radiation, with the exception of the control group, in a single session of 20 Gy. In the Lidocaine Group this drug was administered at a concentration of 2%, intraperitoneally 10 minutes before radiotherapy, dose of 1mg / kg. In the histamine group, the substance was administered subcutaneously at a concentration of 0.5 mg/0.5 mL and a dose of 0.1 mg/kg daily for seven days, starting 24 hours before radiotherapy. Seven and 30 days after radiotherapy the animals were euthanized and their parotids were dissected for morphological analysis and measurement of the nuclear area of acinar cells. Morphological alterations such as acinar disorganization, cytoplasmic vacuolation, suggestive alterations of apoptosis / necrosis and nuclear pleomorphism were observed in the glands of the irradiated rats, with no differences between the groups receiving lidocaine or histamine. Nuclear area of acinar cells was significantly higher in the Lidocaine and Histamine groups. Despite this result, the parotid glands of irradiated animals showed significant mophological changes, regardless of treatment with lidocaine or histamine. The methodology used and results obtained in this study do not support the radioprotective effect of administered substances on the morphology of the rats parotid glands.